2007
DOI: 10.1002/elps.200600526
|View full text |Cite
|
Sign up to set email alerts
|

MEKC combined with SPE and sample stacking for multiple analysis of pesticides in water samples at the ng/L level

Abstract: In this work, a new multiresidue analytical method based on MEKC with UV detection combined with SPE as off-line preconcentration strategy, and reversed-electrode polarity stacking mode (REPSM) as on-line stacking procedure, has been developed for the monitoring of 12 pesticides (carbendazim, pirimicarb, metalaxyl, pyrimethanil, procymidone, nuarimol, azoxystrobin, tebufenozide, fenarimol, benalaxyl, penconazole, and tetradifon) that are currently being used in the Canary Islands (Spain). The optimized MEKC bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Analytes are dissolved in a 1:3 solution made of water/100 mM sodium tetraborate at pH 8.5 v/ v. A high voltage (222 kV) is then applied and the electric current monitored to control sample matrix removal from the capillary. When the current becomes 95-99% of the value obtained with the BGE, the voltage is turned off and the polarity reversed to run the separation [21].…”
Section: Conditions For Repsmmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytes are dissolved in a 1:3 solution made of water/100 mM sodium tetraborate at pH 8.5 v/ v. A high voltage (222 kV) is then applied and the electric current monitored to control sample matrix removal from the capillary. When the current becomes 95-99% of the value obtained with the BGE, the voltage is turned off and the polarity reversed to run the separation [21].…”
Section: Conditions For Repsmmentioning
confidence: 99%
“…This group of pesticides has been previously separated by our team [21] by MEKC and determined in different waters samples using a SPE procedure for off-line preconcentration and reversed-electrode polarity stacking mode (REPSM) as on-line preconcentration strategy. REPSM provided a high sensitivity improvement (LODs between 33.6 and 216 mg/L) with respect to nonstacking conditions (few mg/L).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Ravelo-Pérez et al [86] achieved improved separations of pesticides. Authors demonstrated that the combined use of both, on-column and off-column pre-concentration techniques with MEKC-UV was beneficial to achieve sensitive and simultaneous detection of twelve pesticides, namely, carbendazinm, pirimicarb, metalaxyl, pyrimethanil, procymidone, nuarimol, azoxystrobin, tebufenozide, fenarimol, benalaxyl, penconazol, and tetradifon ( Figure 3).…”
Section: Toxins Contaminants Pesticides and Residuesmentioning
confidence: 99%
“…Recently, RaveloPerez et al [72] proposed the development of a new analytical strategy that combines MEKC-UV analysis with SPE as an off-line preconcentration technique, and reversedelectrode polarity stacking mode (REPSM) as on-line stacking procedure for the simultaneous separation and ultrasensitive determination of 12 pesticides in mineral, stagnant and tap waters. However, GC and HPLC continue being the suggested techniques by official international organizations.…”
Section: Ce)mentioning
confidence: 99%